From Structure to Function: YrbI From Haemophilus influenzae (HI1679) Is a Phosphatase - Parsons, James F. (2002)
The crystal structure of the YrbI protein from Haemophilus influenzae (HI1679) was determined at a 1.67-Å resolution. The function of the protein had not been assigned previously, and it is annotated as hypothetical in sequence databases. The protein exhibits the α/β-hydrolase fold (also termed the Rossmann fold) and resembles most closely the fold of the L-2-haloacid dehalogenase (HAD) superfamily. Following this observation, a detailed sequence analysis revealed remote homology to two members of the HAD superfamily, the P-domain of Ca(2+) ATPase and phosphoserine phosphatase. The 19-kDa chains of HI1679 form a tetramer both in solution and in the crystalline form. The four monomers are arranged in a ring such that four β-hairpin loops, each inserted after the first β-strand of the core α/β-fold, form an eight-stranded barrel at the center of the assembly. Four active sites are located at the subunit interfaces. Each active site is occupied by a cobalt ion, a metal used for crystallization. The cobalt is octahedrally coordinated to two aspartate side-chains, a backbone oxygen, and three solvent molecules, indicating that the physiological metal may be magnesium. HI1679 hydrolyzes a number of phosphates, including 6-phosphogluconate and phosphotyrosine, suggesting that it functions as a phosphatase in vivo. The physiological substrate is yet to be identified; however the location of the gene on the yrb operon suggests involvement in sugar metabolism.